hCeO2@ Cu5.4O nanoparticle alleviates inflammatory responses by regulating the CTSB–NLRP3 signaling pathway - Li, Ying; Xia, Xiaomin; Niu, Zhaojun; Wang, Ke; Liu, Jie; Li, Xue (Frontiers in Immunology, 2024)
Inflammatory responses especially chronic inflammation are closely associated with many systemic diseases. There are many ways to treat and alleviate inflammation, but how to solve this problem at the molecular level has always been a hot topic in research. The use of nanoparticles as anti-inflammatory agents is a potential treatment method. We synthesized new hollow cerium oxide nanomaterials (hCeO2 NPs) doped with different concentrations of Cu5.4O NPs (the molar ratio of Cu/(Ce +Cu) was 50%, 67%, and 83%, respectively), characterized their surface morphology and physicochemical properties, screened the safe concentration of hCeO2@Cu5.4O using the CCK8 method. Macrophages were cultured and P.g-LPS-stimulated were used as a model of inflammation and co-cultured with hCeO2@Cu5.4O NPs, and then observe the effect of the transcription levels of CTSB, NLRP3, Caspase-1, ASC, IL-18 and IL-1β by PCR and detect its effect on the expression level of CTSB protein by Western blot.The levels of IL-18 and IL-1β in cell supernatant were measured by enzyme-linked immunosorbent assay. Our results indicated that hCeO2@Cu5.4O NPs could reduce the production of ROS, inhibit CTSB and NLRP3 to alleviate the damage caused by the inflammatory response to cells. More importantly, hCeO2@Cu5.4O NPs showed stronger anti-inflammatory effects as Cu5.4O NPs doping increased. Therefore, the development of the novel nanomaterial hCeO2@Cu5.4O NPs provides a possible new approach for the treatment of inflammatory diseases.